Penyuluhan Mengenai Pengendalian Emosi Terhadap Kemunculan Ide Bunuh Diri Pada Remaja - Nafsiroh, Affifa; Muhammad Rifa’i Subhi (Concept: Journal of Social Humanities and Education, 2024)
Adolescence is often called a transition period from childhood to adulthood, where many changes occur both psychologically and physically in adolescents. There are new lifestyle changes such as changes in behavior where teenagers feel uncomfortable, resulting in emotional instability which ends in suicide. This research was conducted with the aim of enabling teenagers to overcome the emotions that trigger suicidal ideas. The method used in this research is descriptive qualitative using data and sources in journals and books.